PERANAN DAKWAH DALAM MENINGKATKAN KESADARAN MASYARAKAT TERHADAP KUALITAS LINGKUNGAN DI PUSAT PERBELANJAAN PASAR SENTRAL SENGKANG KABUPATEN WAJO (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This journal was created with the aim of describing how the efforts and methods of da'wah bil hal in increasing public awareness of environmental quality and what factors supporting and inhibiting da'wah bil hal activities in increasing public awareness of environmental quality in the Sengkang Central Market, Wajo Regency. The results of the study show that 1) public awareness of cleanliness already exists but is still part of the entire community in the Sengkang Central Market environment. 2) Da'wah efforts are efforts that can be made as part of da'wah bil hal, namely, a) Get used to maintaining cleanliness and eliminating the habit of littering. b) Providing garbage disposal facilities in public places. c) It should be socialized to the Muslim community that the environment is an important theme discussed in Islam. d) It is necessary to promote environmental care activities such as mutual cooperation in cleaning the market environment. e) processing of waste into useful products. f) Social control by turning on Amar Makruf Nahi Mungkar. 3) Supporting and inhibiting factors for da'wah bil hal activities in Increasing Public Awareness of Environmental Quality in the Central Market, namely, supporting factors, namely: a) support from the community. b) Adequate facilities and infrastructure. While the inhibiting factors are, a) the lack of da'i participation. b) lack of awareness of market visitors. Keywords: the role of da'wah, public awareness, and environmental quality.